The Impact of Social Media Marketing on Brand Loyalty in Fast-Moving Consumer Good (FMCG) Markets - Abasin, Mohammad Moein; Huseynov, Farid (My University, 2020)
Purpose – The aim of this research is to examine the impact of Social Media marketing on consumers’brand loyalty in fast-moving consumer goods (FMCG) markets.Design/methodology/approach – In this study, quantitative research techniques wereused. Primary data of the study was collected through a self-administered Likert type online survey.201 usable responses were collected from volunteer participants familiar with fast-moving consumergoods. The research model of study was analyzed with the help of confirmatory factor analysis(CFA) and structural equation model (SEM) techniques.Findings – The research has shown that two independent variables (Electronic Word of Mouth andCommunity Commitment) influence brand loyalty in fast-moving consumer goods markets. But norelationship has been found between the other two independent variables (Social MediaAdvertisement and Online Brand Community) and brand loyalty.Discussion – In order to sustain brand loyalty, brand owners are using various kinds of marketingtechniques. In addition to these existing efforts, brand owners have started to give more importanceto social media marketing. Social media marketing is a more effective and less expensive way ofreaching customers. The relationship between social media marketing and brand loyalty has drawnattention of both academia and practitioners. To contribute to the existing literature, this studyassessed the role of social media in building brand loyalty in Fast-Moving Consumer Good (FMCG)markets. This study assessed the influence of four different social media marketing factors (OnlineBrand Community, Community Commitment, Social Media Advertisement, and Electronic Word ofMouth) on brand loyalty.
Keywords: İşletme